Drugs availability at districs level and the quality of prescribing in primary health care - Iwan Dwiprahasto, Iwan Dwiprahasto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background: An excessive use of drugs in primary health care is commonly unavoidable. This in part due to the limited knowledge of prescribers who are mostly paramedics and whose pharmacotherapeutic knowldges are limited. More than 90% patients with acute respiratory infection (ARI) and diarrhea received antibiotics and similar percentage of patients with muscle ache received injection unecessarily. Objective: To improve the availability of drugs at district level and to improve the quality of prescribing at primary health centers (PHCs).Design: Quasi experimental with pre and post test analysis and using a control group for comparison. An interactive, problem-based training intervention was carried out within 2 days period involving all PHCs and districts warehouses in three provinces, i.e West Kalimantan, West Sumater, and West Nusa Tenggara. Monitoring, supervision and feedback were carried out regularly upon completion of the inter- vention. This study involves 18 districts and 118 PHCs.Results: 11 .995 prescriptions were collected at baseline, 6 months and 1 year after intervention. An average number of drugs per prescription decreased significantly 1 year after intervention (p<0.05), while no improvement was found in the control group. The use of antibiotics for ARI decreased consis- tently and significantly 6 months and 1 year after intervention (p<0.05). The use of injection for muscle ache also significantly decreased 1 year after intervention (p<0.05). Drug availability at district level could be maintained at an ideal level (1 2-18 months) and no stock out was detected 1 year after the intervention.Conclusions: Interactive, problem-based training on rational use of drugs and training on managing drug supply could improve the quality of prescribing and drug availability at district level.Key words: drug availability - stock out - problem-based training - acute respiratory infection - diarrheaÂ